Los Estereotipos de Género en los Procedimientos Judiciales por Violencia de Género: el Papel del Comité CEDAW en la Eliminación de la Discriminación y de la Estereotipación = Gender Stereotypes in Gender-based Violence Court Proceedings : the CEDAW Committ - Fernández Rodríguez de Liévana, Gema (Oñati Socio-Legal Series, 2015)
This article describes and analyses the CEDAW Committee’s efforts to unveil the use of discriminatory gender stereotypes in domestic violence court proceedings that violate women’s basic rights to access justice. For that purpose, it first examines the concept of gender stereotyping and frames it within a human rights debate, then studies the manner in which gender stereotyping in judicial proceedings is prejudicial to women’s rights. Following this, it explores the international instruments addressing the obligations of States to take all appropriate measures to eliminate gender stereotyping and analyses the Committee’s case-law in domestic violence jurisprudence. Finally, it presents a case-study that the organization "Women’s Link Worldwide" is litigating before the CEDAW Committee and suggests that this is a strategic opportunity for further developing States’ obligations towards the elimination of gender stereotyping.